Penerapan Media Pembelajaran Berbasis Aplikasi Quizizz Dalam Peningkatan Hasil Belajar Pendidikan Agama Islam Dan Budi Pekerti - Damayanti, Nur Yeka; Kustati, Martin; Amelia, Rezki; Gusmirawati; Hidayati; Hayati, Naila (Al-Mau'izhoh: Jurnal Pendidikan Agama Islam, 2024)
The study aims to determine the significant difference in learning outcomes between the experimental class that uses quizizz application-based learning media and the control class that uses conventional learning media for students in grade IX of SMP PGRI 1 Padang. The research method used was a quasi-experiment with a population of 106 students and a research sample of 60 students. Data collection techniques through tests (pretest, posttest) and documentation. The results of the study from the N-gain score data showed that the improvement of learning outcomes in experimental classes that applied quizizz application-based learning media was in a high classification with a percentage of 77%, while the improvement in learning outcomes in control classes that applied conventional learning media was in a low classification with a percentage of 31%.  Supported by the results of the independent sample t-test, a sig. (2 tailed) by 0.000 < 0.05 this means, H-0. rejected and, H-a. Accepted. Thus, the application of quizizz application-based learning media has significant differences in learning outcomes in grade IX students of SMP PGRI 1 Padang.